The future of insurance regulation in the United States - Grace, Martin Francis, 1958-; Klein, Robert Warren, 1953- (Washington, D.C. : Brookings Institution ; Atlanta : Georgia State University, 2009)
"Enhances research and informs the debate on restructuring the framework for U.S. insurance regulation. Evaluates proposed legislation to create an Optional Federal Charter for insurance companies and agents. Also goes beyond discussion of OFC and lays out the broader context and need for regulatory reform in the insurance industry" - Provided by publisher.
Includes bibliographical references and index.
Keywords: Insurance -- State supervision -- United States; Insurance -- Government policy -- United States; Insurance law -- United States